Caleb Cushing papers - Cushing, Caleb, 1800-1879.
Correspondence, memoranda, diaries, journals, writings, speeches, notes, notebooks, legal file, business papers, biographical material, newspaper clippings, printed material, maps, photographs, and other papers reflecting Cushing's role in national and international affairs of the mid-nineteenth century.
Documents Cushing's service as U.S. representative from Massachusetts, commissioner to China, army officer in the War with Mexico, attorney general under Franklin Pierce, minister to Spain, and his work for the administrations of James Buchanan, Abraham Lincoln, and Andrew Johnson. Also documents Cushing's involvement in Democratic and Whig party politics; service as Massachusetts state legislator and associate justice; and diplomatic positions including counsel before a joint British and American commission leading to the Geneva Arbitration Tribunal (1871), special minister to Colombia regarding the proposed Panama Canal (1868), and counsel presenting claims before the United States and Mexican Claims Commission (1868). Includes material pertaining to Cushing's speculation in lands located from Maine to Lower California, his contributions to the North American Review, and his law practice in Newburyport, Massachusetts.
Correspondents include George Bancroft, Benjamin F. Butler, James Campbell, Rufus Choate, Jefferson Davis, James C. Dobbin, Edward Everett, Hamilton Fish, James Guthrie, Francis Lieber, Robert McClelland, Hugh McCulloch, William L. Marcy, Franklin Pierce, Albert Pike, Gideon Johnson Pillow, Sir John Rose, William Henry Seward, Jared Sparks, Roger Brooke Taney, John Tyler, Daniel Webster, and John Greenleaf Whittier.
Microfilm edition of selected correspondence, Dec. 1856-Dec. 1860 (conts. 79-88) available
Microfilm edition of the treaty of Wang Hiya (Wanghsia), 1844 (oversize cont. 164) available
Microfilm produced from originals in the Manuscript Division.
U.S cabinet official and representative from Massachusetts, army officer, diplomat, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Buchanan, James, -- 1791-1868.; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Campbell, James, -- 1812-1893 -- Correspondence; Choate, Rufus, -- 1799-1859 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Dobbin, James C. -- 1814-1857 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Guthrie, James, -- 1792-1869 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Lieber, Francis, -- 1800-1872 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; McClelland, Robert, -- 1807-1880 -- Correspondence; McCulloch, Hugh, -- 1808-1895 -- Correspondence; Marcy, William L. -- 1786-1857 -- Correspondence; Pierce, Franklin, -- 1804-1869 -- Correspondence; Pike, Albert, -- 1809-1891 -- Correspondence; Pillow, Gideon Johnson, -- 1806-1878 -- Correspondence; Rose, John, -- Sir, -- 1820-1888 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Sparks, Jared, -- 1789-1866 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Whittier, John Greenleaf, -- 1807-1892 -- Correspondence; Massachusetts. -- Attorney General's Office; United States. -- Department of Justice. -- Office of the Attorney General; Democratic Party (U.S.); Geneva Arbitration Tribunal; United States and Mexican Claims Commission; Whig Party (U.S.); North American review; Canals -- Panama; Diplomatic and consular service, American; Land speculation; Mexican War, 1846-1848.; Political parties -- United States; China -- Foreign relations -- United States; Colombia -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; Mexico -- Foreign relations -- United States; Massachusetts -- Politics and government -- 1775-1865.; Panama Canal (Panama) -- History; Spain -- Foreign relations -- United States; United States -- Foreign relations -- China; United States -- Foreign relations -- Colombia; United States -- Foreign relations -- Great Britain; United States -- Foreign relations -- Mexico; United States -- Foreign relations -- Spain; United States -- Foreign relations; United States -- History -- Civil War, 1861-1865 -- Claims; United States -- Politics and government -- 19th century; Army officers; Cabinet officers; Diplomats; Lawyers; Representatives, U.S. -- Massachusetts